Meta-Synthesis of Identifying Servant Leadership Components Based on Employees' Innovative Behavior - Torabi, Seyed Meysam; Aramesh, Hamed; Yaghoubi, Nour Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study seeks to systematically review the findings of prior studies on this subject through a meta-synthesis approach, analyzing them based on the formation process and outcomes.Methodology: This research utilizes the meta-synthesis technique and is applied in nature. Accessible and credible documents and records available on websites were examined, focusing on English-language sources from 2010 to 2024 and Persian sources from 2010 to 2024. Among a large number of initial articles, 63 suitable articles were identified. To analyze the selected articles, the concepts, dimensions, and influential components were studied using content analysis. For validating the extracted concepts, a Delphi panel comprising several experts and scholars was employed.Findings: The results indicated four main components: organizational characteristics, leadership style, employee characteristics, and management characteristics. Additionally, experts ranked the importance of servant leadership dimensions based on employees' innovative behavior in the following order: leadership style, management characteristics, employee characteristics, and organizational characteristics.Conclusion: It can be concluded that focusing on the components identified in this research facilitates the development of servant leadership based on employees' innovative behavior.